Identification of hub genes regulating the cell activity and function of adipose-derived stem cells under oxygen-glucose deprivation - Yang, Zhenyu; Lu, Wei; Qi, Zuoliang; Yang, Xiaonan (Frontiers in Molecular Biosciences, 2022)
While oxygen-glucose deprivation (OGD) has been widely utilized in many cell lines to mimic certain biological changes, it has yet to be validated in mesenchymal stem cells. We performed RNA sequencing on adipose-derived stem cells (ADSCs) under hypoxic and glucose-free conditions after 4 h and 8 h. A total of 335 common differentially expressed genes (DEGs) were identified in the two OGD groups compared with the normal control group, consisting of 292 upregulated and 43 downregulated genes. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses indicated that DEGs are mainly involved in metabolic processes, programmed cell death, and DNA-binding transcription activator activity. Protein‒protein interaction and hub gene analysis revealed various potential hub genes, in which response to oxygen levels, the IL-17-related biological function and the hypoxia-inducible factor 1 signaling pathway have been of vital importance. In summary, changes in transcription factor activity may play pivotal roles in oxygen-glucose deprivation. Through RNA sequencing, we have a deeper understanding of the changes in ADSCs after OGD treatment, providing more precise insight into predicting and regulating the stemness of ADSCs.